Peran Psikologi dalam Pencapaian Standar Pendidikan Nasional Gantina Komalasari - Gantina Komalasari (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
Among inmates, there is also silent community of drug users. Banceuy prison is the special prison in the city of Bandung, for inmates related to drug use crime. Recent data has shown that there are a lot of IDUs among inmates, and the cases of HIV positive among those are in the range of 20-53%. [(Banceuy- Bandung prison, 24% (2002); (Indonesian HIV/AIDS Prevention Care Project (IHCP) and Indonesian ealth Department, 2003)]. The Objective are to explore and understand the knowledge, perception and attitude of prison staffs regarding the program of reducing high risk behavior related to HIV among inmates. Method of data gathering is Focus Group Discussion, was collected from 42 out of 115 staffs and the analyze using qualitative approach. The conclusions is sometimes conflict between prison rules and prison staffs understanding, about handling the HIV/AIDS inmates creates uncertainty on implementing the policy (such as in the case of condom and MMT programs).Key-words : Prison staff, IDU's, Inmates, HIV/AIDS